2016
DOI: 10.3758/s13428-016-0817-y
|View full text |Cite|
|
Sign up to set email alerts
|

Subjective age-of-acquisition norms for 600 Turkish words from four age groups

Abstract: The main purpose of this study was to report agebased subjective age-of-acquisition (AoA) norms for 600 Turkish words. A total of 115 children, 100 young adults, 115 middle-aged adults, and 127 older adults provided AoA estimates for 600 words on a 7-point scale. The intraclass correlations suggested high reliability, and the AoA estimates were highly correlated across the four age groups. Children gave earlier AoA estimates than the three adult groups; this was true for high-frequency as well as low-frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 77 publications
(133 reference statements)
2
8
0
Order By: Relevance
“…Since these investigations would require the collection of extensive age-specific norm data, we defer them to future research. Our findings, combined with the explanations offered for the various differences, advocate the use of age-specific norms for lexico-semantic research (see, for instance, De Deyne & Storms, 2007; Gilet, Grühn, Studer, & Labouvie-Vief, 2012; Gobin, Camblats, Faurous, & Mathey, 2017; Göz, Tekcan, & Erciyes, 2017; Grühn & Smith, 2008; Morrow & Duffy, 2005; Söderholm, Häyry, Laine, & Karrasch, 2013).…”
Section: Discussionsupporting
confidence: 58%
“…Since these investigations would require the collection of extensive age-specific norm data, we defer them to future research. Our findings, combined with the explanations offered for the various differences, advocate the use of age-specific norms for lexico-semantic research (see, for instance, De Deyne & Storms, 2007; Gilet, Grühn, Studer, & Labouvie-Vief, 2012; Gobin, Camblats, Faurous, & Mathey, 2017; Göz, Tekcan, & Erciyes, 2017; Grühn & Smith, 2008; Morrow & Duffy, 2005; Söderholm, Häyry, Laine, & Karrasch, 2013).…”
Section: Discussionsupporting
confidence: 58%
“…Age of acquisition (AoA) is one of the most frequent measures of individual words for which norms have been provided and continue to be collected, especially subjective AoA norms collected in adults (e.g., Göz, Tekcan, & Erciyes, 2016 for a recent collection of AoA norms in Turkish). AoA and word frequency (objective and subjective frequency measures) for individual words are correlated variables, with the result that one variable needs to be controlled for when investigating the influence of the other.…”
mentioning
confidence: 99%
“…In other words, those words, respectively, hold an advantage to be accessed and processed easier than less frequently used, later learned, abstract, and less imageable ones. Furthermore, several lines of evidence demonstrate that these lexical properties, including concreteness, frequency, and imageability are so closely related that it is often challenging to measure and distinguish the effect of one variable from the other ( Gernsbacher, 1984 ; Göz et al, 2017 ). For instance, Morrison and Ellis (1995) argue that earlier studies that showed frequency effects (i.e., faster processing of commonly used words) demonstrated such results as they failed to control for AoA.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, concreteness and imageability are also two variables that have been almost used interchangeably by many researchers due to their high correlation as concrete items are easier to evoke an image in mind than abstract items ( McMullen and Bryden, 1987 ; Fliessbach et al, 2006 ; Reilly and Kean, 2007 ). Besides, AoA can also pose as a confounding variable for concreteness and imageability measures based on the fact that early acquired words are mostly concrete, and hence, mostly imageable ( Bird et al, 2001 ; Bonin et al, 2004 ; Göz et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%